Bringing Ethics of Global Governance Back In: A Case Study of the Republic of China (Taiwan) - Huang, Kwei-Bo (Contemporary Chinese political economy and strategic relations, 2020)
This paper touches on the ethical dimension of global governance and calls for a study or (re-)examination of the lack of Taiwan's participation in institutions of global governance. The first section explains the meaning of ethics of global governance, followed by the second section that uses four commonly seen ethical discussions in global governance - i.e., the "actor problem", the "speech act problem", the "accountability fragmentation" issue, and the "universal application" issue - to scrutinize the case of Taiwan that has been largely excluded from the mainstream international society for almost fifty years. Then, this papers provides an idealistic remedy, a "post-international universe" with greater participation and power sharing of non-state actors, while emphasizing the political reality in which major power politics cannot be neglected.